Trans-Synaptic Regulation of Metabotropic Glutamate Receptors by Elfn Proteins in Health and Disease - Matsunaga, Hayato; Aruga, Jun (Frontiers in Neural Circuits, 2021)
Trans-regulation of G protein-coupled receptors (GPCR) by leucine-rich-repeat (LRR) transmembrane proteins has emerged as a novel type of synaptic molecular interaction in the last decade. Several studies on LRR-GPCR interactions has revealed their critical role in synapse formation and establishing synaptic properties. Among them, LRR-GPCR interactions between extracellular leucine-rich repeat fibronectin domain-containing family proteins (Elfn1 and Elfn2) and metabotropic glutamate receptors (mGluRs) are particularly interesting as they can affect a broad range of synapses through the modulation of signaling by glutamate, the principal excitatory transmitter in the mammalian central nervous system. Elfn-mGluR interactions have been investigated in hippocampal, cortical, and retinal synapses. Postsynaptic Elfn1 in the hippocampus and cerebral cortex mediates the tonic regulation of excitatory input onto somatostatin-positive interneurons through recruitment of presynaptic mGluR7. In the retina, presynaptic Elfn1 binds to mGluR6 and is necessary for synapse formation between rod photoreceptor cells and rod-bipolar cells. The repertoire of binding partners for Elfn1 and Elfn2 includes all group III mGluRs (mGluR4, mGluR6, mGluR7, and mGluR8), and both Elfn1 and Elfn2 can alter mGluR-mediated signaling through trans-interaction. Importantly, both preclinical and clinical studies have provided support for the involvement of the Elfn1-mGluR7 interaction in attention-deficit hyperactivity disorder (ADHD), post-traumatic stress disorder (PTSD), and epilepsy. In fact, Elfn1-mGluR7-associated disorders may reflect the altered function of somatostatin-positive interneuron inhibitory neural circuits, the mesolimbic and nigrostriatal dopaminergic pathway, and habenular circuits, highlighting the need for further investigation into this interaction.